Emergency blood transfusion service (report) (1939)
1939 1939 1930s 5 pages EMERGENCY BLOOD TRANSFUSION SERVICE. Generally For some months past the Ministry of Health have been pushing forward the organization of a Service to make available blood for transfusion purposes in emergency. In the London Area four depots have been set up at each of which about 2,000 pints of blood are kept under refrigeration, and this blood is available on demand to the Hospitals in the area. Depots are also being set up throughout the country at important towns and cities. Blood donors have been registered and grouped, and blood put into store. Each area hospital and its satellite hospitals have been collecting and storing blood on a smaller scale, but in extremely few cases has it been possible for these hospitals to make proper provision for storing the blood. Since they have lost many, if not all, of their former patients and received no casualties to replace them, they have been able to utilize for blood storage, cold rooms, cold cabinets and domestic type refrigerators from ward kitchens. Firstly it is clear that as soon as casualties start coming in, these cold stores will be wanted for foodstuffs in the normal way. Secondly in very few cases are these refrigerators entirely suitable for blood storage, with consequently a very high percentage of wastage. Many hospitals throughout the country have expressed a desire to instal [install] properly designed refrigeration equipment for blood storage, realizing the shortcomings of their existing facilities and the need for reducing wastage to an absolute minimum. The action which they can take, however, is limited by financial difficulties, and in almost every case the feeling is that whilst it is highly desirable to have a special blood storage cabinet, nothing can be done without financial assistance. It appears that the Ministry of Health do not intend that any grant should be made to assist the hospitals to provide this very essential equipment although the cost is not high, and consequently the whole Emergency Blood Transfusion Service is handicapped by the lack of proper storage facilities where they are most needed. 292/845.2/4/51